PITUITARY METASTASIS: CENTRAL DIABETES INSIPIDUS UNMASKED BY CORTICOSTEROIDS - CASE SERIES AND REVIEW OF LITERATURE - N, Shree Vidhya; JK, Tan; RA, Raja Nurazni; M, Masni (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Metastasis to the pituitary is rare and is most common amongst the elderly population with advanced malignancy. An estimated 1% of pituitary tumours resected are metastatic. Primary sites that frequently metastasize include breast and lung carcinomas. Advancement with multiple modalities of therapy has led to prolonged survival of patients with advanced malignancy. Herein, we present three cases and review of literature of pituitary metastases presenting as central diabetes insipidus (CDI) incidentally unmasked following administration of corticosteroids. CASE Three cases of CDI in pituitary metastases were presented. A total of 9 cases published from 2007-2018 were reviewed. Search resulted in 161 articles, ultimately, 18 pertinent references relevant to this research. The objective; establish common clinical features, presentation variations and natural progression of disease. Nine reported cases of CDI unmasked by corticosteroids from 2007 to 2017 along with the present 3 cases were reviewed. There was equal gender prevalence with a mean age of 61 years old. More than 75% of cases described had previously been diagnosed with advanced malignancies. The remaining 25% presented with varying symptoms of hypopituitarism as harbinger to discovery of the primary neoplasm. Amongst cases presented, primary malignancies with pituitary metastases included lung adenocarcinoma (33%), breast carcinoma (25%), nasopharyngeal carcinoma (16%), renal cell carcinoma (8%), hepatocellular carcinoma (8%) and gastric adenocarcinoma (8%). It is noteworthy that two of the three presented cases were the result of direct infiltration of nasopharyngeal carcinoma to the pituitary. There is limited data documenting the prevalence of nasopharyngeal carcinoma with pituitary metastasis within the Asian population. CONCLUSION CDI unmasked by corticosteroids is less recognized, potentially lethal but fully reversible complication of pituitary metastasis. Symptoms or signs of CDI should be sought in all patients with advanced malignancies presenting with polyuria and hypernatremia. Prompt restoration of pituitary hormones is warranted to allow timely restoration of hormonal balance and preventing endocrine emergencies.